การเปรียบเทียบสมรรถนะทางความร้อนของท่อเทอร์โมไซฟอนแบบหน้าตัดกลม และแบบหน้าตัดเหลี่ยมด้วยเทคนิคการถ่ายภาพทางความร้อน THERMAL PERFORMANCE COMPAIRISION OF RECTANGULAR AND CIRCULAR THERMOSYPHON USING THERMAL IMMAGING TECHNICS - พิพัฒน์ไพบูลย์, นำพน; แดงทน, วิริยะ; ทองแดง, สัณหวัจน์; มีแสง, มงคล (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Thermosyphon has been developed a shape on the specific working with different cross-sectional areas such as circle and square. Many researchers were interesting about study to continue an application. This research presents the thermal performance results of the difference cross section area as square tube of 37.5 mm. and circle tube diameter of 37.5 mm. Comparison the thermal performance with thermal imaging analysis technique. The thermosyphon was made of stainless-steel material with total length of 1,200 mm. Ethanol was using as fluid with filling ratios of 50% of evaporator section and the evaporator temperature of 60oC, inclination angles of 0, 45 and 90 degrees from horizontal. The results showed that the thermal performance of circle tube thermosyphon was clearly higher than square tube thermosyphon, these results was confirmed by the thermal images and measuring the surface temperature, at evaporator section the surface temperature of circle and square cross section area similarly results However, at the surface temperature of condenser section was higher than square tube thermosyphon in any inclination angles when the circle tube temperature of 55-60oC and 30-40oC of square tube, therefore the heat transfer of circle cross section area was higher than square cross-section area, the results confirmed clearly with the comparison of the surface temperature measured and the thermal image and thermal image analysis can be applying of another experiment in the future.